2011
DOI: 10.1111/j.1742-481x.2011.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Braden scale score and pressure ulcer development in patients admitted in trauma intensive care unit

Abstract: The purpose of this study was to determine the relationship between the scores of Braden scale and pressure ulcer development among critically ill patients. All patients who admitted to intensive care unit (ICU) in 3 months (during July-October 2010) were surveyed with Braden scale. Patients who gained higher score of Braden scale were at lower risk for pressure ulcer development compared with the other patients. Braden scale is a useful tool for predicting pressure ulcer development in trauma ICU patients. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 14 publications
4
26
0
2
Order By: Relevance
“…Patients of ICU are always at risk of rare skin problems such as pressure ulcer because of their unconsciousness or being sedated (1–3); therefore, they are unable to self‐report their skin problems. Our patient showed that even chest lead could result in skin problems, which in turn increases the responsibility of ICU nurses to consider more skin care in critically ill patients.…”
mentioning
confidence: 99%
“…Patients of ICU are always at risk of rare skin problems such as pressure ulcer because of their unconsciousness or being sedated (1–3); therefore, they are unable to self‐report their skin problems. Our patient showed that even chest lead could result in skin problems, which in turn increases the responsibility of ICU nurses to consider more skin care in critically ill patients.…”
mentioning
confidence: 99%
“…Subsequently, research [12][13][14][15][16][17][18] has been focused on additional risk factors observed in ICU patients to develop a new critical care risk scale. In 2 studies, 12,13 oxygen and perfusion variables were examined as risk factors for pressure ulcers.…”
mentioning
confidence: 99%
“…Limited data are available that describe the complete time frame for pressure injury manifestation, especially for deep tissue injury . The Braden Scale has been used to predict pressure injury risk in critically ill patients . Ranzini found that although the original Braden scale measured at ICU admission was a valuable tool for predicting pressure injuries in critically ill patients, it was not as accurate for patients on a ventilator, those receiving renal replacement therapy, or surgical patients.…”
Section: Literature Reviewmentioning
confidence: 99%